2013
DOI: 10.3136/fstr.19.591
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Compound Natural Preservative Solution to Chilled Beef and Mutton Under Vacuum Packaging During Refrigerated Storage

Abstract: A compound natural preservative (CNP) was produced by mixing clove cinnamon extracts with tea polyphenol, chitosan, propolis, nisin and lysozyme. Its effects on microbiological [total aerobic counts (TACs)], chemical [total volatile base nitrogen (TVB-N), 2-thiobarbituric reactive substances (TBARS), total reducing activity (TRA) and pH values], and colorimetric characteristics of chilled beef and mutton that were kept under vacuum packaging during refrigerated storage at 4 ± 1℃ were investigated for 4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This result was similar to the total aerobic and anaerobic count results. Because the TVB‐N is related to the spoilage by bacterial decomposition of the meat muscle, higher values of the total aerobic and anaerobic counts should correspond with a higher TVB‐N during storage (Hao et al., ). Our results suggested that the active film incorporated with plantaricin BM‐1 and chitosan has good potential for active packaging of chilled meat to inhibit the growth of L. monocytogenes and background spoilage bacteria to prolong the shelf life of fresh meat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was similar to the total aerobic and anaerobic count results. Because the TVB‐N is related to the spoilage by bacterial decomposition of the meat muscle, higher values of the total aerobic and anaerobic counts should correspond with a higher TVB‐N during storage (Hao et al., ). Our results suggested that the active film incorporated with plantaricin BM‐1 and chitosan has good potential for active packaging of chilled meat to inhibit the growth of L. monocytogenes and background spoilage bacteria to prolong the shelf life of fresh meat.…”
Section: Discussionmentioning
confidence: 99%
“…The pH and TVB-N are the most important indicators that determine the deterioration of cold fresh meat (Dong et al, 2016;Hao, Yang, Yang, & Ma, 2013). With time, the pH of the meat showed a tendency to increase gradually ( Figure 4) and had significant differences with the total aerobic and anaerobe counts, which may have been caused by small molecules such as amino acids and alkaline groups from the proteins and enzymes (Kumar & Tanwar, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TVB‐N value is one of the most widely used indicators for assessment of meat deterioration. As a result of the degradation of proteins and nonprotein nitrogenous compounds, which are chiefly caused by spoilage microbial activity, some volatile basic nitrogenous substances were produced, e.g., ammonia, and primary, secondary and tertiary amines (dimethylamine, trimethylamine), which lead to the meat deterioration (Hao et al, ). Figure indicates that the values of TVB‐N increased monotonically in all groups with the storage time.…”
Section: Resultsmentioning
confidence: 99%
“…[1] For this reason, various methods have been used throughout the history to preserve meat. There are a limited number of traditional products in which meat is conserved in fat after being cooked.…”
Section: Introductionmentioning
confidence: 99%